2022
DOI: 10.29333/ejgm/12337
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, perceived barriers, and practices of oncology nurses regarding cancer pain management

Abstract: Effective cancer pain management involves significant knowledge and proficiency in pain assessment and recording. This study sought to assess nurses' knowledge, behaviors, and perceived impediments to managing cancer-related pain.Methods: A descriptive, cross-sectional design was used. A convenience sample of 502 nurses working in three primary health care sectors in Jordan was selected to ensure national representation. To collect data, an Englishlanguage online Google Electronic Form was employed.Results: Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Othman and Al-Atiyyat (2022) found that nurses working in Jordan had an average knowledge score of 6.48, indicating limited knowledge in this area. [ 13 ] The study also identified significant knowledge gaps related to opioid rescue dosage and the fastest route of action for opioids. [ 13 ] In Jordan, doctors demonstrated better knowledge and attitudes towards pain management compared to nurses, with doctors having a stronger understanding of ‘opioid addiction’ and nurses having better grasp of ‘combined analgesics’.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Othman and Al-Atiyyat (2022) found that nurses working in Jordan had an average knowledge score of 6.48, indicating limited knowledge in this area. [ 13 ] The study also identified significant knowledge gaps related to opioid rescue dosage and the fastest route of action for opioids. [ 13 ] In Jordan, doctors demonstrated better knowledge and attitudes towards pain management compared to nurses, with doctors having a stronger understanding of ‘opioid addiction’ and nurses having better grasp of ‘combined analgesics’.…”
Section: Search Resultsmentioning
confidence: 99%
“…[ 13 ] The study also identified significant knowledge gaps related to opioid rescue dosage and the fastest route of action for opioids. [ 13 ] In Jordan, doctors demonstrated better knowledge and attitudes towards pain management compared to nurses, with doctors having a stronger understanding of ‘opioid addiction’ and nurses having better grasp of ‘combined analgesics’. [ 14 ] Similarly, in Ethiopia, Admass et al .…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations